Homeoprophylaxis—Can You Believe It? - Cecchetto, Elena (Homœopathic Links, 2015)
I have written this essay to deconstruct an aspect of my clinical practice. There is controversy around the use of homeoprophylaxis in preventing disease during epidemics and pandemics. I wanted to see if there was research that could demonstrate the ability to use homeopathy in epidemics/pandemics. If so, what type of research and can it be recognised as valid? If it is not, why not? I explored and gathered information, interviews with practitioners, charts, essays, population studies and randomised controlled trials. These helped see the various levels of ability for homeopathic remedies to be used in order to prevent infectious diseases in a laboratory and in actual contemporary populations. However, these studies are in contrast within the prevailing paradigm to do with how homeopathic remedies work. Because there is an underlying disbelief in the idea that highly diluted substances could work, there is a difficulty in accepting the studies that demonstrate success for homeopathic remedies.
Keywords: Homeoprophylaxis; Prevention; Epidemics; Pandemics